2023
DOI: 10.1183/23120541.00738-2022
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis lung transplantation waitlist mortality, a national registry database study

Abstract: The Lung Allocation Score prioritizes lung transplantation candidates balancing waitlist-mortality and post-transplant survival. The score groups sarcoidosis candidates based on mean pulmonary artery pressure: ≤30 mmHg (Sarcoidosis A) are grouped with COPD and >30 mmHg (Sarcoidosis D) with idiopathic pulmonary fibrosis. We hypothesize that sarcoidosis candidates have a higher waitlist-mortality than other candidates within their LAS grouping. This is a retrospective cohort study of consecutive lung transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Indeed, sarcoidosis is grouped within this system with other end-stage lung diseases according to the mean pulmonary artery pressure value: when <30 mmHg (group A sarcoidosis), patients are grouped with COPD, whereas when >30 mmHg (sarcoidosis group D), they are grouped with IPF. This study showed that group D had the highest mortality on the waitlist, and the authors suggested a revision of sarcoidosis LT candidates grouping in allocations systems [112] to mitigate waitlist mortality disparity. (7) Holistic management of APS In all cases, the treatment of APS requires a holistic and comprehensive management of all dimensions of the disease (symptoms, psychological distress, fatigue).…”
Section: (6) Lung Transplantation (Lt)mentioning
confidence: 79%
See 1 more Smart Citation
“…Indeed, sarcoidosis is grouped within this system with other end-stage lung diseases according to the mean pulmonary artery pressure value: when <30 mmHg (group A sarcoidosis), patients are grouped with COPD, whereas when >30 mmHg (sarcoidosis group D), they are grouped with IPF. This study showed that group D had the highest mortality on the waitlist, and the authors suggested a revision of sarcoidosis LT candidates grouping in allocations systems [112] to mitigate waitlist mortality disparity. (7) Holistic management of APS In all cases, the treatment of APS requires a holistic and comprehensive management of all dimensions of the disease (symptoms, psychological distress, fatigue).…”
Section: (6) Lung Transplantation (Lt)mentioning
confidence: 79%
“…Survival after LT in sarcoidosis is similar to that of other ILDs, but two factors are predictive of worse survival: older age and the extent of preoperative lung fibrosis [111], suggesting again to take them into account when considering referral to a LT expert center. Interestingly, the LAS has been recently challenged [112]. Indeed, sarcoidosis is grouped within this system with other end-stage lung diseases according to the mean pulmonary artery pressure value: when <30 mmHg (group A sarcoidosis), patients are grouped with COPD, whereas when >30 mmHg (sarcoidosis group D), they are grouped with IPF.…”
Section: (6) Lung Transplantation (Lt)mentioning
confidence: 99%
“…Following the implementation of the lung allocation score (LAS) in 2005, a greater percentage of sarcoidosis patients received lung allografts, leading to reduced waitlist mortality [ 119 ]. However, recent studies have found that, compared with patients with COPD and IPF, individuals with sarcoidosis continue to face disproportionately higher waitlist mortalities [ 120 ]. The several factors contributing to waitlist mortality were identified as pulmonary hypertension, poorer functional status, oxygen dependence, lower reduced output, and female sex [ 121 , 122 ].…”
Section: Managementmentioning
confidence: 99%